2019
DOI: 10.1016/j.celrep.2019.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates the Satellite Cell Compartment in Females

Abstract: SUMMARY Skeletal muscle mass, strength, and regenerative capacity decline with age, with many measures showing a greater deterioration in females around the time estrogen levels decrease at menopause. Here, we show that estrogen deficiency severely compromises the maintenance of muscle stem cells (i.e., satellite cells) as well as impairs self-renewal and differentiation into muscle fibers. Mechanistically, by hormone replacement, use of a selective estrogen-receptor modulator (bazedoxifene), and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 87 publications
(106 reference statements)
1
77
1
2
Order By: Relevance
“…However, they found no difference in strength loss between E2-treated and untreated 20 month-old female mdx mice after 9 ECC indicating that E2 is not protective to muscle when challenged simultaneously by aging and dystrophin deficiency [ 49 ]. Indeed, recovery of strength was impaired in OVX mdx mice relative to sham mdx mice in the current study, consistent with our previous work in wild-type (WT) mice demonstrating that OVX mice recovered ~20% less isometric torque 1–3 weeks after injury compared to sham mice or E2-treated OVX mice [ 34 , 35 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, they found no difference in strength loss between E2-treated and untreated 20 month-old female mdx mice after 9 ECC indicating that E2 is not protective to muscle when challenged simultaneously by aging and dystrophin deficiency [ 49 ]. Indeed, recovery of strength was impaired in OVX mdx mice relative to sham mdx mice in the current study, consistent with our previous work in wild-type (WT) mice demonstrating that OVX mice recovered ~20% less isometric torque 1–3 weeks after injury compared to sham mice or E2-treated OVX mice [ 34 , 35 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Salimena et al found in 6 week-old mdx mice, that OVX mdx mice had decreased regenerating fibers compared to control female mdx mice [53]. This decrease in regenerating fibers in OVX mice supports the notion that estrogen deficiency compromises the ability of skeletal muscles to functionally recover after injury in mdx and WT female mice [34,35,50].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to reproductive function, ovarian steroids have been shown to target a number of tissues (e.g., epithelial, connective, muscle and nervous; [ 2 4 ]) and influence an array of biological processes (e.g., metabolism, ventilation, immunity, cognition, gastrointestinal, cardiovascular, autonomic regulation, and genitourinary function; [ 5 – 13 ]). As such, different concentrations of circulating ovarian steroids throughout the lifespan and across the menstrual cycle (with and without dysfunction and/or manipulation) might significantly influence the mechanisms that control and regulate cell function and integrated physiologic adaptation in women.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenic obesity has direct consequences on the health of menopausal and post-menopausal women (12). Interestingly, estradiol is also involved in the modulation of the local and systemic inflammatory responses thus affecting sarcopenia (13,14).…”
Section: Introductionmentioning
confidence: 99%